Impact of pH on the viability and morphology of blastocystis isolates - Farah Haziqah, Meor Termizi; Chandrawathani, Panchacharam; Douadi, Benacer; Govind, Suresh Kumar; Wilson, John James; Mohd Khalid, Mohd Khairul Nizam; Rajamanikam, Arutchelvan; Lewis, John Watkin; Mohd Zain, Siti Nursheena (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Blastocystis sp. is ubiquitous in avian, mammalian and human hosts and propagates in either neutral or slightly alkaline conditions within the host’s gastro-intestinal tract. Of the few previous studies on this enteric protozoan parasite in feline and canine hosts, prevalence values have been shown to range between 0 to 70.8%. In view of the close association between humans, and canine and feline hosts as companion animals, faecal samples of 180 Felis catus and 82 Canis lupus, collected from Penang and Kuala Lumpur, Malaysia, were initially screened by in vitro cultivation followed by molecular characterization. No positive isolates were identified in culture but in 12 feline samples DNA barcoding detected a zoonotic subtype Blastocystis ST1 for the first time. Consequently, avian and human isolates, which had previously been successfully cultured, were used to investigate the impact of pH on the viability and morphology of Blastocystis sp. The use of Trypan blue showed that the number of viable cells increased when exposed to pH 4 and a significant increase in viability occurred in pH values of 5 to 7. Development of Blastocystis cells in both isolates was suppressed in media less than pH 5 followed by the disappearance of viable cells from avian isolates in more acidic media below pH 4. Morphologically at pH 4 cells from avian isolates were less rounded, and with wrinkled / shrunken surfaces, than the more normal rounded cells from human isolates. On the other hand, at values below pH 3, no viable cells in human isolates were visible. The present findings therefore confirm that gastro-intestinal pH is an important determinant of Blastocystis viability and consequently influences the epidemiology of infection within avian, mammalian and human hosts.